New Azores archipelago daily precipitation dataset and its links with large‐scale modes of climate variability. (8th February 2016) - Hernández, Armand; Kutiel, Haim; Trigo, Ricardo M.; Valente, Maria A.; Sigró, Javier; Cropper, Thomas; Santo, Fátima Espírito
ABSTRACT: Within the scope of the two major international projects of long‐term reanalysis for the 20th century coordinated by the National Oceanic and Atmospheric Administration and European Centre for Medium‐Range Weather Forecasts, the Instituto Dom Luiz from the University of Lisbon has digitized a large number of long‐term daily and monthly climate records from stations in Portugal and former Portuguese colonies. We have recently finished the digitization of precipitation values from Ponta Delgada (capital of the Azores Archipelago), obtaining an almost complete daily precipitation series, with the exception of some years (1864–1872; 1878–1879; 1888–1905; 1931; 1936; and 1938) for which only monthly values are available. At daily resolution, we have used a comprehensive assessment on different characteristics of rain spells (consecutive days with rainfall accumulation). The distribution of precipitation presents an evident seasonal pattern and reveals large inter‐annual and intra‐annual variability, increasing considerably in the last 3 decades. The frequency of dry years decreases almost by half between the first and the second part of the record, whereas wet years increase up to three times. This is mainly due to more intense events that are reflected by higher rain‐spell yields (amount of precipitation) and rain‐spell intensity (amount of precipitation per day) values. Most of the extreme precipitation events occurred during the last 2 decades, and they generally correspond to dates with cyclonic conditions over the North Atlantic. We have also looked into the influence of large‐scale modes of climate variability on the precipitation regime of the Azores Archipelago. As expected, theNorth Atlantic Oscillation (NAO) has a major impact on the precipitation regime of Ponta Delgada both in winter and summer. However, our results show a non‐stationary NAO influence and the impact of other large‐scale modes (including the Atlantic Multidecadal Oscillation and El Niño‐Southern Oscillation) increases when this influence becomes weaker.